2019
DOI: 10.3390/cancers11091369
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of the Autotaxin-Lysophosphatidic Acid Signaling Axis

Abstract: The revelation that microRNAs (miRNAs) exist within the human genome uncovered an underappreciated mechanism of gene expression. For cells to regulate expression of their genes, miRNA molecules and argonaute proteins bind to mRNAs and interfere with efficient translation of the RNA transcript. Although miRNAs have important roles in normal tissues, miRNAs may adopt aberrant functions in malignant cells depending on their classification as either a tumor suppressor or oncogenic miRNA. Within this review, the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…ATX upregulation also correlates to dysregulated microRNA regulation, favoring a pro-tumorigenic state [75,76]. A thorough review on the micoRNA regulation of the ATX-LPA signaling axis has recently been published [77].…”
Section: Maladaptive Effects Of Excessive Atx Secretion and Lpa Signamentioning
confidence: 99%
“…ATX upregulation also correlates to dysregulated microRNA regulation, favoring a pro-tumorigenic state [75,76]. A thorough review on the micoRNA regulation of the ATX-LPA signaling axis has recently been published [77].…”
Section: Maladaptive Effects Of Excessive Atx Secretion and Lpa Signamentioning
confidence: 99%
“…Thus, together with our data, this suggests that allosteric regulation may predominate in controlling ATX activity, although other mechanisms of post‐transcriptional regulation may also play a role. Recent studies have found that Atx is a known or predicted target of micro RNA that can inhibit mRNA translation, including MiR‐29a/b/c, MiR‐489‐3p, and MiR‐101‐3p (reviewed in (Murph, )). Future work investigating whether these MiR are induced by fasting will provide additional insight into mechanisms underlying nutritional regulation of ATX activity.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it plays a key role in the regulation of autotaxin, a major producer of lisophosphatidic acid (LPA). 50 , 51 Both, autotaxin and LPA are known to be increased in the aqueous humor of open-angle glaucoma patients. Inhibition of autotaxin has been shown to increase aqueous outflow ex vivo.…”
Section: Discussionmentioning
confidence: 99%